2012
DOI: 10.1002/cbic.201100725
|View full text |Cite
|
Sign up to set email alerts
|

An Enzyme Catalyzing O‐Prenylation of the Glucose Moiety of Fusicoccin A, a Diterpene Glucoside Produced by the Fungus Phomopsis amygdali

Abstract: Isoprenoids form the largest family of compounds found in nature. Isoprenoids are often attached to other moieties such as aromatic compounds, indoles/tryptophan, and flavonoids. These reactions are catalyzed by three phylogenetically distinct prenyltransferases: soluble aromatic prenyltransferases identified mainly in actinobacteria, soluble indole prenyltransferases mostly in fungi, and membrane-bound prenyltransferases in various organisms. Fusicoccin A (FC A) is a diterpene glycoside produced by the plant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…xanthones) [66,67] or to O-and N-functional groups of aromatic moieties [68,69]. More recently, an enzyme was identified that catalyzes O-prenylation of a glucose moiety of the diterpene fusicoccin A [70]. Mechanistic and structural studies revealed that these proteins adopt a new β-barrel fold containing repeating αββα-secondary structure elements, which gives this enzyme family their name: ABBA-type.…”
Section: Aromatic Prenyltransferasesmentioning
confidence: 97%
See 1 more Smart Citation
“…xanthones) [66,67] or to O-and N-functional groups of aromatic moieties [68,69]. More recently, an enzyme was identified that catalyzes O-prenylation of a glucose moiety of the diterpene fusicoccin A [70]. Mechanistic and structural studies revealed that these proteins adopt a new β-barrel fold containing repeating αββα-secondary structure elements, which gives this enzyme family their name: ABBA-type.…”
Section: Aromatic Prenyltransferasesmentioning
confidence: 97%
“…8). This cluster was identified in the draft genome sequence of P. amygdali based on a previously identified ABBA-type prenyltransferases that catalyzed in vitro the reverse O-prenylation of glucose with DMAPP [70], which is a prenylation that is also present in fusiccocin A. A combination of in vitro assays with recombinant enzymes and gene disruption allowed Dairi's group to then establish the complete fusicoccin A pathway [189].…”
Section: Fusicoccanes and Other Diterpenoids Made By Monofunctional Ementioning
confidence: 99%
“…23) Mycelia of the transformants were inoculated into a medium (3.5% Czapek-Dox, 2% starch, 1% polypeptone; final volume 100 mL) and cultivated at 30°C for 3 d in a reciprocal shaker (125 strokes/min). cDNA preparation was performed by a method described previously, 30) with the primer set shown in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…These include the well-studied gibberellin pathways found in several fungi that use a bifunctional diterpene synthase that combines the domains of a class I and class II terpene synthases (which are separate enzymes in plant diterpene biosynthesis) to cyclize GGPP [111][112][113]. Mining of Ascomycota genomes followed by gene deletion studies and stepwise heterologous coexpression of pathway genes in Aspergillus has led to the elucidation of additional gene clusters involved in the biosynthesis of the diterpene compounds fusicoccin, brassicicene, aphidicolin and phomopsene [54,55,[114][115][116][117][118][119][120], and a sesterterppenoid (C 25 ) [121]. Intriguingly, these terpenoid scaffolds are built by a novel-type of chimeric terpene synthases that combines the domains of a class I terpene synthase and a prenyldiphosphate synthase that provides the C 25 isoprene substrate for the cyclase [55].…”
Section: Terpene Synthases and Terpenoid Biosynthetic Clustersmentioning
confidence: 99%